2005
DOI: 10.1111/j.1742-4658.2005.04688.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutinin‐33 of type A botulinum neurotoxin complex binds with synaptotagmin II

Abstract: Botulinum neurotoxin type A (BoNT/A), the most toxic substance known to mankind, is produced by Clostridium botulinum type A as a complex with a group of neurotoxin‐associated proteins (NAPs) through polycistronic expression of a clustered group of genes. NAPs are known to protect BoNT against adverse environmental conditions and proteolytic digestion. Hemagglutinin‐33 (Hn‐33) is a 33 kDa subcomponent of NAPs that is resistant to protease digestion, a feature likely to be involved in the protection of the botu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Previous protection and transmission electron microscopy studies have shown detailed interactions of BoNT/D NTNH and HA70 (Hasegawa et al, 2007; Niwa et al, 2007); HA33 was shown to bind epithelial cells, possibly bringing the toxin in close proximity to its receptors (Matsumura et al, 2008; Zhou et al, 2005). Perhaps the larger BoNT/B complex, with presumably more NAP proteins, can bind intestinal membranes with a higher affinity than the BoNT/A complexes.…”
Section: Discussionmentioning
confidence: 98%
“…Previous protection and transmission electron microscopy studies have shown detailed interactions of BoNT/D NTNH and HA70 (Hasegawa et al, 2007; Niwa et al, 2007); HA33 was shown to bind epithelial cells, possibly bringing the toxin in close proximity to its receptors (Matsumura et al, 2008; Zhou et al, 2005). Perhaps the larger BoNT/B complex, with presumably more NAP proteins, can bind intestinal membranes with a higher affinity than the BoNT/A complexes.…”
Section: Discussionmentioning
confidence: 98%
“…HA‐33/HA‐17 arms facilitated cell binding in addition to transport through the cell layer. Zhou et al . (2005) isolated synaptotagmin II using a pull‐down assay from the rat brain synaptosomal protein extract as a putative protein receptor for HA‐33 on nerve cells.…”
Section: Discussionmentioning
confidence: 99%
“…44 A reasonable explanation for this observation is that the BoNT/A in the sample, was partially in complex form containing hemagglutinin-33, which is a neurotoxin-associated protein that can bind synaptotagmin II and trigger cellular responses. 45 This suggests that the p21-Fc has the potential to detect both of BoNT/A complex in addition to BoNT/B. But the cell sensor presensitized with p21-Fc was limit to distinguish these two type of BoNTs.…”
Section: Detection Of Bont/b By the Mast Cell Biosensormentioning
confidence: 99%